A NEW SPECIES OF ADINANDRA (PENTAPHYLACACEAE) FROM INDIA. (7th November 2014) - Pathak, M. K.; Bhaumik, M.; Krishna, G.
<x content-type="archive" xml:space="preserve">Abstract</x> A new species, Adinandra kamalae M.K.Pathak, Bhaumik & G.Krishna (Pentaphylacaceae), is described from Upper Siang District, Arunachal Pradesh, India.